Digital Nikah and Smart Contracts: Legal Reconstruction of Islamic Marriage in the Blockchain Era - Gunawan, Tri; Muchimah; Dewi Nita Utami; Panggih Abdiguno; Abdulnasir Dhaw Alsayd (Islamic Law and Social Issues in Society, 2025)
The digital era is transforming the institution of marriage, as online ceremonies without official registration create an urgent legal crisis involving fasād al-nasab (distortion of lineage), violations of women’s rights, and a lack of legal certainty. This paper aims to reconstruct Islamic marriage law by integrating blockchain-based smart contracts, assessing the validity of al-‘aqd al-raqmī (digital contract) through the lenses of fiqh al-mu‘āmalāt, legal pluralism, and smart legal contract theory. Employing a qualitative-descriptive methodology, primary data were drawn from Islamic legal texts, fatwas, state regulations, and blockchain technical documentation—collected via literature review and document analysis from authoritative sources such as Tarjih Muhammadiyah fatwas, Patricia Pixie (2024), and Blockchain Council reports (2024). Data were analyzed using a tri-theoretical framework—Wahbah al-Zuhaili’s transactional jurisprudence, Sally Falk Moore’s theory of legal pluralism, and Kevin Werbach’s smart legal contract theory—synthesized within the concept of tadākhul al-anṣāṭ al-qānūniyyah (overlapping legal systems). Findings indicate that digital marriage can be ṣaḥīḥ (valid) under Islamic law if it fulfills shurūṭ al-ṣiḥḥah (conditions of validity), and that blockchain can serve as a sijill al-‘adl (register of justice) due to its immutability (lā yuqbal al-ta‘dīl); however, without state recognition, such unions remain ghayr saḥīḥ qānūniyyan (legally invalid). Limitations include reliance on secondary data and the absence of standardized sharī‘ah-compliant digital identity protocols. Future research should pilot-test this model and examine al-mas’ūliyyah al-shar‘iyyah (Islamic legal liability) in cases of coding errors.